Comparison of Estrogen and Progesterone Receptors Status between Cell-Blocks of Fine Needle Aspiration and Tissue-Blocks of Corresponding Mastectomy Specimen in Invasive Ductal Breast Cancer - Imtiaz Malik, Ayesha; Tabbassum, Tahira; Raza, Syed Hyder; Iqbal, Sahar; . , Rukhsana (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer is one of the common causes of mortality in female population, world-wide. Pakistan has highest incidence among Asian countries. Majority of breast cancers belong to invasive ductal carcinoma type. Estrogen and Progesterone nuclear receptors are important expression tools for molecular categorization of invasive breast carcinoma. Aim: To correlate status of estrogen and progesterone receptor expression between FNA cell-blocks and tissue blocks from mastectomy specimen in invasive ductal carcinoma of female breast. Methods: In current study, carried out at Pathology Department of Niazi Medical and Dental College, Sargodha from August, 2018 to July,2020, 125 cell blocks of FNA and tissue blocks of corresponding mastectomy specimens of invasive ductal breast carcinoma were included. Routine H & E staining protocol was adopted for microscopic diagnosis.24 Estrogen and Progesterone receptor expression was evaluated by immunohistochemistry25. Data was analyzed by using SPSS-20 version. Results: Spearman’s correlation showed a strong positive relationship between status of ER (rs = .959, p<.001) and PR expression (rs = .958, p < .001) observed in fine needle aspirate cell-blocks and in corresponding tissue blocks of mastectomy specimen. Conclusion: The study concluded that as there is concordance in ER and PR expression status, hence, FNA cell-blocks are reliable for planning hormonal treatment strategies instead of tissue blocks in invasive ductal breast carcinoma.